2022
DOI: 10.1155/2022/6703409
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Obstetric Fistula on the Overall Quality of Life among Survivors Who Had Undergone Obstetric Fistula Repair, Central Gondar Zone, Northwest Ethiopia, 2020: A Community-Based Study

Abstract: Introduction. Childbirth is a special time in the lives of women and families at large. It can also be a time of great tragedy. International reports show that, annually, more than 500,000 women die from pregnancy and childbirth complications globally. For every woman who dies in childbirth, majorities remain alive, but scarred by permanent disabilities. Obstetric fistula is, without a doubt, the most severe of pregnancy-related disabilities. Objective. This research is aimed at assessing the long-term effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In our study, most women were divorced, which is consistent with previous OF research in Nigeria, Ghana, and Ethiopia [ 39 41 ]. While most divorces in our study occurred before surgical intervention, aligning with prior OF studies in Ethiopia and Uganda, in some cases, divorce followed successful surgical correction, not necessarily due to OF but rather other sexual and reproductive health issues, such as infertility [ 34 , 41 , 42 ]. Researchers in Tanzania and Malawi have documented ongoing sexual and reproductive health issues post-OF surgery, including infertility and sexual dysfunction [ 40 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, most women were divorced, which is consistent with previous OF research in Nigeria, Ghana, and Ethiopia [ 39 41 ]. While most divorces in our study occurred before surgical intervention, aligning with prior OF studies in Ethiopia and Uganda, in some cases, divorce followed successful surgical correction, not necessarily due to OF but rather other sexual and reproductive health issues, such as infertility [ 34 , 41 , 42 ]. Researchers in Tanzania and Malawi have documented ongoing sexual and reproductive health issues post-OF surgery, including infertility and sexual dysfunction [ 40 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Due to this, immediate embrace of women following surgery is not easy (13). To address this, the project in Tanzania conducted seminars, campaigns, advocacy and counselling sessions to families and communities where the survivors came from.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of data from six studies [18,36,44,52,62,69] showed that married women were 44% more likely to have a successful surgical repair of obstetric fistula than their single counterparts. The positive impact of marital status on successful outcome might be justified by a husband's psychological and financial support, as indicated by studies that investigated the quality of life following the surgical repair of obstetric fistula patients [110][111][112]. However, none of the included studies demonstrate a significant association, clearly implying that a repeat study involving a large number of participants should be performed to investigate whether marital status determines the success of surgical repair of obstetric fistula.…”
Section: Plos Onementioning
confidence: 99%